Penyelesaian Sengketa antara Bank SharÃ®âah dengan Nasabah Bermasalah melalui Badan Arbitrase SharÃ®âah Nasional (BASYARNAS) menurut UU No. 30 tahun 1999 - Sulistyowati, Sulistyowati (ISLAMICA: Jurnal Studi Keislaman, 2014)
This study deals with dispute settlement between Bank Syariâah and its customers through the National Shariâah Arbitration Board (BASYARNAS). It focuses to elaborate the procedures of dispute settlement between Bank Syariâah and its customers of financing from the perspective of Islamic law according to Bill No. 30/1999 above law No. 30 year 1999. Based on procedures as mentioned in the bill with regard to arbitration and alternative dispute resolution, Basyarnas, in proofing and resolving cases, has fulfilled the procedures and satisfied the conflicting parties with justice, so there is no need to appeal and reconsideration. This means that Basyarnas has conducted dispute resolution according to the existing procedures. The dispute settlement has also been in accordance with the QurâÃ¢n and other Islamic legal rules which consist of the principles of power and mandate applied by the arbitrator in deciding and resolving the dispute. The boardâas an independent institutionâhas setttled the disputes on the basis of justice for all parties, rejected the act of bribery since the cost is measurable. In addition, Basyarnas also gives strong emphasis on the principle of equality, friendship, consistence and response-bility in resolving disputes.